Proactive Mapping and Preventive Ablation Reduce Defibrillator Implantation Rates in Tetralogy of Fallot - Kimura, Yoshitaka; Wallet, Justin; Brouwer, Charlotte; Bokma, Jouke P.; Bertels, Robin A.; Jongbloed, Monique R.M.; Hazekamp, Mark G.; Blom, Nico A.; Zeppenfeld, Katja (Journal of the American College of Cardiology, 2025)
In patients with repaired tetralogy of Fallot (rTOF) and spontaneous ventricular tachycardia (VT), transection of slow-conducting anatomical isthmus (SCAI) by ablation results in excellent long-term VT-free survival. In patients without prior VT, proactive electroanatomical mapping and preventive SCAI ablation may impact patient selection for primary prevention implantable cardioverter-defibrillator (ICD) implantation. The purpose of this study was to evaluate long-term outcomes after proactive electroanatomical mapping and ablation of SCAI and its impact on patient selection for primary prevention ICD implantation, compared with current risk stratification methods in rTOF patients without prior VT. Consecutive rTOF patients without prior VT who underwent electroanatomical mapping for VT substrate identification were included (2005-2020). After successful SCAI ablation, ICD implantation was offered but was subject to shared decision making. The potential eligibility for ICD implantation was retrospectively determined using the following: 1) a clinical risk score; 2) guideline-recommended risk factors (American Heart Association [AHA] 2018 guidelines without late gadolinium enhancement [LGE] on cardiac magnetic resonance [CMR] information, AHA 2018 guidelines with LGE-CMR information, European Society of Cardiology [ESC] 2022 guidelines); and 3) electroanatomical mapping and SCAI ablation results. In the latter, patients with a nontransected SCAI, VT substrates remote from anatomical isthmuses, or severe right-/left ventricular dysfunction qualified for ICDs. A total of 97 patients were included (age 35 ± 16 years, 57 men); 33 patients (34%) had SCAI and 19 (20%) had inducible monomorphic VT (17 of 19 SCAI-dependent VT). Successful SCAI transection was achieved in 87% (26 of 30 patients) in whom attempted, without complications. In total, 13 patients received an ICD implantation. During a median follow-up of 58 months (Q1-Q3: 30-99 months), 4 patients (4%) had VT, all after ablation failure. According to clinical risk score, AHA 2018 guidelines without LGE-CMR information, AHA 2018 guidelines with LGE-CMR information, and ESC 2022 guidelines, 49 (51%), 24 (25%), 31 (32%), and 48 patients (49%) would have qualified for ICDs, respectively. After proactive mapping and preventive ablation, 11 patients (11%) remained ICD candidates, including all 4 with a VT event during the follow-up (annual VT risk 7%/y). Long-term outcome of rTOF patients without SCAI is excellent. Proactive electroanatomical mapping and preventive SCAI ablation may significantly reduce primary prevention ICD implantation rates compared with current risk prediction methods. [Display omitted]